PEMIKIRAN EKONOMI ISLAM KONTEMPORER MENUJU SERTIFIKASI HALAL BERBASIS KEARIFAN LOKAL - Muhammad Affandi AR; Nasrullah Bin Sapa, Mukhtar Lutfi (Jurnal Ekonomi dan Bisnis, 2025)
This study aims to examine contemporary Islamic economic thought in supporting the implementation of halal certification based on local wisdom. Halal certification is not only a religious aspect but also an economic strategy to enhance the competitiveness of local products in the global market. This approach integrates Islamic economic principles, such as justice, sustainability, and public welfare, with unique local potentials to ensure the quality of halal products. This research employs a qualitative method with a descriptive-analytical approach, referring to relevant literature and case studies on the implementation of halal certification in various regions of Indonesia. The findings indicate that the implementation of halal certification based on local wisdom not only increases consumer trust but also empowers local communities through the preservation of culture and traditions. Furthermore, collaboration among religious scholars, the government, and business actors is key to achieving an inclusive and sustainable halal certification system. Therefore, this concept can serve as a model for other countries in developing an economy rooted in Islamic values relevant to contemporary challenges.